2013
DOI: 10.1561/0100000069
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Resource Allocation in Coordinated Multi-Cell Systems

Abstract: The use of multiple antennas at base stations is a key component in the design of cellular communication systems that can meet high-capacity demands in the downlink. Under ideal conditions, the gain of employing multiple antennas is well-recognized: the data throughput increases linearly with the number of transmit antennas if the spatial dimension is utilized to serve many users in parallel. The practical performance of multi-cell systems is, however, limited by a variety of nonidealities, such as insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
320
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(321 citation statements)
references
References 226 publications
(452 reference statements)
0
320
0
1
Order By: Relevance
“…However, in practice, hardware suffers from impairments; for example, phase noise, IQ imbalance, and amplifier non-linearities [4][5][6]. These have a deleterious impact on the achievable performance [7][8][9][10][11][12][13]. This effect is more pronounced in high-rate systems, especially those employing inexpensive hardware [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in practice, hardware suffers from impairments; for example, phase noise, IQ imbalance, and amplifier non-linearities [4][5][6]. These have a deleterious impact on the achievable performance [7][8][9][10][11][12][13]. This effect is more pronounced in high-rate systems, especially those employing inexpensive hardware [5].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is more pronounced in high-rate systems, especially those employing inexpensive hardware [5]. For instance, some recent works have demonstrated that non-ideal hardware severely affects single-hop multiantenna systems; [6,8] proved that there is a finite capacity limit at high SNR, while [9,13] showed that existing signal processing algorithms need to be re-designed to account for these impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the conclusions in Section III-A, (8) shows that D2D mode is optimal when the interference received at UE 2 is much smaller than the one received at the base station, i.e., I D2D I ul . By solving (8) as a quadratic equation, we have…”
Section: B D2d Optimality With a Shared Resourcementioning
confidence: 81%
“…As shown in [8], the optimization problems (P1) and (P2) are tightly connected [8]: let the optimal solution to (P1) with transmit power p * UE be denotedR * , then the optimal solution to (P2) with the QoS levelR * is exactly p * UE . Nevertheless, we show that these optimization problems behave differently in terms of when D2D mode is preferable over cellular mode, and vice versa.…”
Section: A System Modelmentioning
confidence: 99%
See 1 more Smart Citation